Developing a male-specific counselling curriculum for HIV treatment in Malawi [version 1; peer review: awaiting peer review] - Misheck Mphande; Julie Hubbard; Isabella Robson; Elijah Chikuse; Eric Lungu; Morna Cornell; Khumbo Phiri; Thomas J Coates; Sam Phiri; Kathryn Dovel (Gates Open Research)
Background Men living with HIV in sub-Saharan Africa have sub-optimal engagement in antiretroviral therapy (ART) programs. Generic ART counselling in Malawi does not meet men’s needs. Methods We developed a male-specific ART counselling curriculum, adapted from the Malawi Ministry of Health curriculum, based on literature review of men’s needs and motivations for treatment. We piloted the curriculum with men in six communities, with focus group discussions to assess knowledge of ART, motivators and barriers to care, and perceptions of the male-specific curriculum (n=85). We analysed data in Atlas.ti using grounded theory. We finalised the curriculum in a half-day meeting with Ministry and partner stakeholders (n=5) and implemented it in two randomized trials (IDEaL and ENGAGE). We describe the steps to develop, test and finalize the curriculum. Results We adapted three existing topics (status disclosure, treatment as prevention, and ART side effects) and added four new topics (how treatment contributes to men’s goals, feeling healthy on treatment, navigating health systems, and self-compassion for the cyclical nature of lifelong treatment). Key motivators included: family wellbeing, having additional children, being financially stability, and earning/keeping respect. Men reported little prior understanding of how ART contributed to their personal goals, and were most interested in treatment as prevention, benefits of disclosure/social support, how to navigate health systems, and side effects with new regimens. Respondents stated that the male-specific counselling challenged the idea that men were incapable of overcoming treatment barriers to lifelong medication. Conclusion Men need male-specific ART counselling curriculum to address their needs and increase access to and retention in HIV care. In the Malawi context, topics should include how treatment contributes to men’s goals, navigating health systems, self-compassion for lifelong treatment, and taking treatment while healthy. Other countries with high HIV burdens and limited resources could follow the steps outlined in this paper. This curriculum is being evaluated within the two randomized trials.